Dietary polyphenols to combat the metabolic diseases via altering gut microbiota. (November 2019) - Gowd, Vemana; Karim, Naymul; Shishir, Mohammad Rezaul Islam; Xie, Lianghua; Chen, Wei
Abstract: Background: Metabolic syndrome (MetS) is defined as the cluster of metabolic disorders that consist of insulin resistance, hyperglycemia, dyslipidemia, central adiposity, and hypertension, which is associated with metabolic diseases (MD). Gut microbiota (GM) has a profound effect on human metabolism. The composition and function of GM play a critical role in MD, but the mechanisms have not been fully understood yet. Microorganisms that colonize the human gut play a pivotal role in the digestion and absorption of dietary polyphenols (PPs). GM is capable of metabolizing high-molecular-weight PPs into more biologically active metabolites. As a result, phenolic metabolites can modulate the growth of GM. PPs are naturally occurring compounds that are available in food, such as fruits and vegetables. PPs intake is inversely associated with metabolic syndrome (MetS) via modulating GM. Scope and approach: In this review, we present an overview of the evidence supporting the GM dysbiosis during MD. In addition, health-beneficial effect of PPs against MD via modulating the GM is discussed. Key findings and conclusions: Literature evidence supports PPs as novel and strategic molecules in the prevention and treatment of MD. This is explained not only by their anti-obesity, anti-oxidative, anti-inflammatory, anti-diabetes, and anti-hypercholesterolemic effects but also by their ability to improve and inhibit the growth of beneficial and pathogenic bacteria. Although, there are numerous studies defines the effective role of PPs against MD via altering the GM, a significant research effort on GM is still needed to consider PPs as promising nutraceuticals against MD. Highlights: Dietary factors have significant influence on gut microbiota. Gut dysbiosis contributes to the development of metabolic diseases. Phenolic gut metabolites are more biologically active than parent compounds. Polyphenols can modulate the composition of gut microbiota. Polyphenols act against metabolic diseases via altering gut microbiota.